Pelatihan Media Digital Multimodal Interaktif Bagi Guru SD - Hotimah Hotimah; Erma Suryani Sahabuddin; Rahmawati Patta; Siti Raihan; Hikmawati Usman (Civiliza Publishing, 2026)
This community service activity aimed to improve teachers’ digital competencies through interactive multimodal digital media training at SDN Aoeropala, Makassar City. The training involved 15 teachers from various grade levels. The activity was carried out through several stages, namely needs analysis, socialization, training, hands-on practice, mentoring, and evaluation. The needs analysis was conducted using the Mentimeter platform to identify teachers’ experiences in using digital media and the training needs required. The results of the analysis indicated that teachers still experienced limitations in developing interactive digital learning media, particularly in the use of Artificial Intelligence (AI), educational game development, interactive flipbooks, and VR/AR-based media. The training was conducted intensively from morning until 4:00 PM (WITA) using a workshop-based hands-on method with various applications such as Canva AI, Padlet, Quizizz, Heyzine Flipbook, QR Code, and Augmented Reality (AR)-based Assembler Edu. In addition to face-to-face training, participants also received continuous mentoring through a WhatsApp group to support the independent development of learning media products. The results showed that the interactive multimodal digital media training was able to improve teachers’ understanding and skills in developing more creative, interactive, and innovative multimodal learning media. Teachers also demonstrated high enthusiasm in implementing educational technology and were able to produce digital media products as the final assignment of the training. Therefore, this activity is expected to support the development of an adaptive and sustainable digital learning culture in elementary schools.